2018
DOI: 10.1002/cbdv.201800407
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activities of Isoflavonoids from Uromyces striatus Infected Alfalfa

Abstract: Fungal pathogens constitute a severe yield‐limiting factor for the pasture crop alfalfa (Medicago sativa L.). Eleven phenolic compounds, including a new isoflavane, were isolated from the Uromyces striatus Schroet. infected alfalfa. The effect of infection with U. striatus Schroet. on the phytochemical profile of alfalfa was investigated using ultra‐performance liquid chromatography (UPLC), and the antifungal properties of isolated compounds against a range of pathogens were tested. It was found that the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The 13 C-NMR and distortionless enhancement by polarization transfer (DEPT) spectra of 1 showed 18 carbon signals (Table 2) attributed to 3 × OCH 3 , 2 × CH 2 (one oxygen-bearing), 6 × CH (five aromatic methines), and 7 × C (five oxygenated aromatic carbons). These spectroscopic data indicated that compound 1 was an isoflavane possessing a hydroxy and three methoxy groups [18,19,20]. Comparison of the 1 H and 13 C-NMR data of 1 and sativan [18] suggested that an additional methoxy group was substituted at C-8 in 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The 13 C-NMR and distortionless enhancement by polarization transfer (DEPT) spectra of 1 showed 18 carbon signals (Table 2) attributed to 3 × OCH 3 , 2 × CH 2 (one oxygen-bearing), 6 × CH (five aromatic methines), and 7 × C (five oxygenated aromatic carbons). These spectroscopic data indicated that compound 1 was an isoflavane possessing a hydroxy and three methoxy groups [18,19,20]. Comparison of the 1 H and 13 C-NMR data of 1 and sativan [18] suggested that an additional methoxy group was substituted at C-8 in 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the top 10 upregulated metabolites in the treatment group were homogentisic acid, N-feruloylagmatine, icariside B2, 3,4-dihydroxybenzeneacetic acid, 4-O-glucosyl-4-hydroxybenzoic acid, 1-O-salicyloyl-β- d -glucose, 1-O-galloyl-β- d -glucose, 3-O-galloyl- d -glucose, and medicarpin-3-O-glucoside (Figure D). We focused on the 100 metabolites upregulated by chitosan, and most of them were categorized as phenolic acids, alkaloids, flavonoids, lignans, and coumarins (Table S2), which were extensively involved in fungal resistance and plant immunity. These findings hinted that chitosan could induce the production of antifungal compounds to control the C. heterostrophus infection and development in maize.…”
Section: Resultsmentioning
confidence: 99%
“…28 In addition, the contents of several phenolic compounds in Uromyces striatus-infected alfalfa were higher than those in healthy alfalfa, and these phenolic compounds exhibited a moderate inhibitory activity against fungal pathogens. 29 Moreover, coumarins also exhibited excellent inhibitory activity against phytopathogens. 31,32 All these results would better explain why chitosan has such strong disease resistance activity.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The spectral data (MS, 1 H, and 13 C‐NMR spectra) of compounds 1 – 13 were identical to those reported in the previous literature. Consequently, their structures were identified as those of 5α,8α‐epidioxy‐(22E,22R)‐ergosta‐6,22‐dien‐3β‐ol ( 1 ), [34] gigantenol ( 2 ), [35] (3β,22E)‐ergosta‐5,7,22‐trien‐3‐ol ( 3 ), [36] 5,6‐epoxy‐(3β,5α,6α,7α,22E)‐ergosta‐8,22‐diene‐3,7‐diol ( 4 ), [37] 5α,6α‐epoxyergosta‐8(14),22‐diene‐3β,7α‐diol ( 5 ), [38] 5,6‐epoxy‐3‐hydroxy‐(3β,5α,6α,22E)‐ergost‐22‐en‐7‐one ( 6 ), [39] 7α‐methoxy‐5α,6α‐epoxyergosta‐8(14),22‐dien‐3β‐ol ( 7 ), [40] isolumichrome ( 8 ), [41] adenosine ( 9 ), [42] palmitic acid ( 10 ), [42] n‐octacos‐9‐enyl propionate ( 11 ), [43] n‐eicosanoic‐9‐enoic acid ( 12 ), [44] and 5,8,11‐hexacosatrienoic acid ( 13 ) [44] . Among these isolated compounds, a large amount of them ( 1 ‐ 4 , 6 , 8 , 9 , and 12 ) were tested for their antifungal activity against P. infestans .…”
Section: Resultsmentioning
confidence: 99%